Quercetin effectiveness in patients with COVID-19 associated pneumonia - Zupanets, I. A.; Holubovska О. А.; Tarasenko, O. O.; Bezuhla, N. P.; Pasichnyk, M. F.; Karabynosh, S. O.; Kopcha, V. S.; Moroz, L. V.; Maksymchuk, H. V.; Kobrynska, O. Ya.; Fishchuk, R. M.; Schulha, D. I.; et al. (Zaporozhye Medical Journal, 2021)
The aim of this work was to evaluate the effectiveness of quercetin addition to the treatment regimen for patients with COVID-19 associated pneumonia. Materials and methods. The effectiveness of two dosage forms of quercetin was studied in 200 patients, who were divided equally into the main and control groups. The main group patients received quercetin in addition to the basic therapy: intravenous drip of Quercetin/Polyvinylirolidone during the first 10 days followed by oral administration of Quercetin/Pectin over the next 10 days. Patients from the control group received only the basic therapy drugs. The study evaluated the dynamics of the disease symptoms (saturation level, respiratory rate, body temperature, cough, general weakness), as well as laboratory markers (C-reactive protein (CRP), ferritin, D-dimer). Results. Two dosage forms of quercetin consistently used in addition to the basic therapy improve pulmonary gas exchange and accelerate the lung function recovery. This is evidenced by a statistically significant majority of patients with positive dynamics in the symptoms of “Saturation level” and “Cough” as well as the meeting a complex indicator of the therapy effectiveness 2 days earlier than in the control group. The treatment regimen applied also helps to stabilize the level of D-dimer in the blood of the main group patients. Conclusions. The use of two dosage forms of quercetin in addition to the basic therapy accelerates the recovery of patients with coronavirus disease associated pneumonia and can help to prevent the progression of COVID-19 associated coagulopathy.